Speech and hearing science as related to clinical audiology and speech and language pathology - Herbert F Oyer; Daniel S Beasley (Journal of All India Institute of Speech and Hearing, 1970)
It is the intent of the authors to comment generally upon the relevance of thediscipline of speech and hearing science as the principal substratum upon whichthe professions of speech and language pathology and audiology are built. Thisis not meant to deny the importance of other areas that contribute informationsuch as physics, anatomy, neurophysiology, linguistics, or psychology; for in orderto explore the important correlates of speech, language, and audition one mustcall upon information provided for by these disciplines. In a sense, the speechand hearing scientist, if properly prepared, is one who can deal meaningfullywith those elements of the other disciplines that bear significantly upon hisinquiries into events of speech, language, or audition